The influence of n/p ratio on the synthesis and growth processes of chlorella sp. alga, isolated from the Black Sea - Mihnea, Pia Elena; Voinescu, Iulia (Cercetări Marine - Recherches Marines, 2026)
Preliminary results on the influence of N/P ratio in marine unicellular algae Chlorella sp. are presented. The authors correlate the culture growth stadium with mainly cellular compounds synthesis.